Association between CUBN gene variants, type 2 diabetes and vitamin D concentrations in an elderly Greek population. Issue 198 (April 2020) - Tsekmekidou, Xanthippi; Tsetsos, Fotis; Koufakis, Theocharis; Karras, Spyridon N.; Georgitsi, Marianthi; Papanas, Nikolaos; Papazoglou, Dimitrios; Roumeliotis, Athanasios; Panagoutsos, Stylianos; Thodis, Elias; Theodoridis, Marios; Pasadakis, Ploumis; et al.
Highlights: 95 SNPs within the CUBN gene were genotyped in 716 patients with T2DM and 542 controls. rs11254375, rs7071576, rs6602175, rs1801224 and rs4366393 were linked to T2DM risk. rs41301097 was strongly associated with higher 25(OH)D levels. Abstract: Accumulating evidence suggests a potential implication of vitamin D biological network in the pathogenesis of diabetes mellitus. The megalin-cubilin endocytotic system constitutes a key transport structure, with a modulating role in vitamin D metabolism. We aimed to assess the contribution of variants in the CUBN gene to the genetic risk of Type 2 Diabetes Mellitus (T2DM). 95 polymorphisms within CUBN were genotyped in 716 patients with T2DM and 542 controls of Greek origin. Samples were analyzed on Illumina Human PsychArray. Permutation test analysis was implemented to determine statistical significance. Twenty-five-hydroxy-vitamin-D [25(OH)D)] levels were measured in a sub-group of participants (n = 276). Permutation analysis associated rs11254375_G/T (pemp = 0.00049, OR = 1.482), rs6602175_G/T (pemp = 0.016, OR = 0.822), rs1801224_G/T (pemp = 0.025, OR = 0.830), rs4366393_A/G (pemp = 0.028, OR = 0.829) and rs7071576_A/G (pemp = 0.04, OR = 1.219) with T2DM. Mean 25(OH)D concentrations were significantly lower in patients with T2DM compared to controls (16.70 ± 6.69 ng/ml vs 18.51 ± 6.71 ng/ml, p < 0.001), although both groups were vitamin D deficient. In a further quantitative analysis, rs41301097 was strongly associated with higher 25(OH)D concentrations (p = 5.233e-6, beta = 15.95). Our results indicate a potential role of CUBN gene in T2DM genetic susceptibility in the Greek population. These findings may also denote an indirect effect of vitamin D metabolism dysregulation on the pathogenesis of T2DM. Further studies are required to replicate our findings and clarify the complex underlying mechanisms.